Optimalisasi Produksi “Jakulawak” Dan “Jahe Merah” Di Desa Sinsingon Barat Kecamatan Passi Timur Kabupaten Bolaang Mongondow - Pantow, Hendrik Josua; Loho, Agnes Estephina; Rengkung, Leonardus Ricky (AGRI-SOSIOEKONOMI, 2024)
This research aims to determine the optimal production amount of instant herbal drink products "Jakulawak" and "Red Ginger". This research was conducted in Sinsingon Village, East Passi District, Bolaang Mongondow Regency, and carried out during June 2023. The data used in this research is primary data which is how the product is made, production quantity, price of production raw materials, product selling price, number of workers, availability of raw materials used, labor hours and tools, availability of labor and working time for tools to be used by interviewing the owners of the herbal drink business "Jakulawak" and "Red Ginger". The secondary data used in this research was taken from google scholar, which is previous research and literature reviews related to the research topic, namely production optimization. The research results show the optimal combination of two types of products based on the availability of existing resources, namely X1 (Jakulawak) with a value of 14 and X2 (red ginger) with a value of 0 with the Z value (maximum profit) obtained being IDR 329,347.